Improving bond performance of ribbed steel bars embedded in recycled aggregate concrete using steel mesh fabric confinement. (10th March 2023) - Fayed, Sabry; Madenci, Emrah; Onuralp Özkiliç, Yasin; Mansour, Walid
Highlights: Using SMF to improve the bond behaviour of recycled aggregate concrete is the main topic of this work. Bond strength, bond stress-slip response, and ductility of unconfined/confined pull out specimens were all tested. All confined specimens' ultimate bond strengths were higher than those of unconfined specimens. The maximum increasing rate in the ductility of confined specimens containing 0–100% RCA was 117.7%. A novel proposed equation is derived to estimate the ultimate bond strength of RAC. Abstract: To investigate the bond behaviour of passively confined-recycled aggregate concrete (RAC), centre pull out tests were carried out on deformed steel bar with a diameter (Ø) of 12 mm. The recycled concrete aggregate (RCA) replacement ratios are 0, 30, 50, and 100 %. To investigate local bond strength, a short anchorage bonded length (La) of 10 was chosen. Steel mesh fabric (SMF) cylinders were used to confine the RAC around the bonded length of the bar. SMFs have diameters of 4Ø and 6Ø. SMF cylinder reinforcement ratios were estimated to be 0, 2.33, 3.04, 3.5, and 4.56 %. To accurately estimate maximal rising ratios in bond strength response owing to RAC confinement using SMFs, all specimens are intended to fail in the pull out mode (rather than the splitting mode). Unconfined and confined pull out specimens were tested for failure mechanism, ultimate local bond strength, bond stress-slip response, and ductility. When compared to similar unconfined specimens, confinement utilising SMFs dramatically improved bond stress-slip behaviour for all specimens including RCA. Ultimate bond strengths of RAC-unconfined specimens were 3.7–24.5 % lower than those of NAC-unconfined specimens, whereas ultimate slips of RAC-unconfined specimens were 25–140 % higher than those of NAC-unconfined specimens. Due to the usage of SMF cylinders at various levels of RCA, the ultimate bond strength of all confined specimens was dramatically increased when compared to unconfined specimens. When compared to a control unconfined NAC-specimen, the ductility of unconfined specimens containing 30 %, 50 %, and 100 % RCA decreased by 5.7, 18.6, and 39.6 %, respectively. In comparison, when compared to similar unconfined specimens, the maximum rising ratios in the ductility of confined specimens containing 0 % RCA, 30 % RCA, 50 % RCA, and 100 % RCA are 44.2 %, 77.9 %, 52.4, and 117.7 %, respectively. A novel proposed formula is developed to compute the ultimate bond strength of RAC while taking into account the influence of concrete grade, RCA content, concrete confinement via SMF, and transverse ties, and its results agree with the experimental results.